2007
DOI: 10.1016/j.envpol.2006.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the in situ, time-integrated DGT technique by monitoring changes in heavy metal concentrations in estuarine waters

Abstract: Various natural and anthropogenic processes influence heavy metal concentrations within estuaries. In situ, time-integrated DGT measurements made over concurrent tidal phases found significantly higher concentrations of Cu (probability p=0.017), Zn (p=0.003) and Ni (p=0.003) during the flood phase, because the incoming tide passes several point sources. DGT-reactive Cu concentrations significantly decreased with increased tidal-flushing and vice versa within a marina (correlation r=-0.788, p=0.02). DGT measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
3
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 27 publications
2
52
3
3
Order By: Relevance
“…A key difficulty in interpreting results for this purpose will be the temporal factor, as the DET and DGT technique measure over a relatively long period (hours) in potentially very dynamic systems. It is not possible to extract temporal information about discrete events from a single probe, so combining the data with measurements made using temporally discrete techniques, such as microelectrodes, or using systematic repeated probe deployments, as in Dunn et al (2003), may be necessary. There are some limitations on the application of this technique in the field.…”
Section: Discussionmentioning
confidence: 99%
“…A key difficulty in interpreting results for this purpose will be the temporal factor, as the DET and DGT technique measure over a relatively long period (hours) in potentially very dynamic systems. It is not possible to extract temporal information about discrete events from a single probe, so combining the data with measurements made using temporally discrete techniques, such as microelectrodes, or using systematic repeated probe deployments, as in Dunn et al (2003), may be necessary. There are some limitations on the application of this technique in the field.…”
Section: Discussionmentioning
confidence: 99%
“…Some excellent papers on methods for determining free metal ion concentration, labile species fraction, metal complexation capacity in waters, and sediment flux have been published [218,[249][250][251][252][253][254][255][256][257][258][259][260][261][262]. A wide range of biomimetic approaches exists [263].…”
Section: Tools For Experimental Designsmentioning
confidence: 99%
“…12 Because of recent increases in the amount of Cu used in antifouling paints, the concentration of this element is high in the waters around marinas and port areas. 47 In addition, Warnken et al 6 and Dunn et al 19 demonstrated a direct relationship between the DGT-Cu and DGT-Zn concentrations and the number of recreational boats in marinas. Both Cu and Zn found in paints produce a synergic effect on organisms.…”
Section: Dgt-labile Metal Concentrationsmentioning
confidence: 99%
“…In total, 6 deployments were carried out, two in each seasonal period. Following a conceptual model of the distribution and behavior of dissolved metals vs. salinity in the Patos Lagoon estuary, the range of salinity was classified as low (0-6), intermediate (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) or high (above 25). 22 In each deployment period, four devices were attached to a rope fixed on a pier at 0.5 m depth about 10 m from the margin area of the estuary.…”
Section: Dgt Deploymentmentioning
confidence: 99%
See 1 more Smart Citation